Odpowiedź :
Odpowiedź:
a)
2^2 + a^2 = (sqrt(5))^2
4 + a^2 = 5
a^2 = 1
a = 1
b)
x^2 + 12^2 = 15^2
x^2 + 144 = 225
x^2 = 225 - 144 = 81
x = 9
c)
5^2 + 7^2 = c^2
25 + 49 = c^2
c^2 = 74
c = sqrt(74) , [sqrt - pierwiastek]
d)
5^2 + a^2 = (sqrt(50))^2 [sqrt - pierwiastek]
25 + a^2 = 50
a^2 = 25
a = 5
Szczegółowe wyjaśnienie:
Odpowiedź:
Szczegółowe wyjaśnienie:
a)
2² + a²= √5²
a²=√5²-2²
a²=5-4
a²=1
a=1
b)
x²+ 12²= 15²
x²=225-144
x²= 81
x = 9
c)
5²+7²=c²
25+49=c²
74=c²
c=√74
d)
a²+5²=√50²
a²+25=50
a²=25
a=5